Legal Protection For Employees Affected by Layoffs or Layoffs Reviewed From The Perspective of The Job Creation Law - I Nyoman Adi Muliana Kusuma; I Nyoman Bagiastra (Fakultas Hukum, Universitas Warmadewa, 2025)
The focus of this study is to analyze legal certainty for the relevant community regarding legal protection if affected by layoffs (Termination of Employment). This study applies normative legal research methods with a legislative, conceptual, and analytical approach. The conclusion of the study explained that legal certainty for people affected by layoffs undertaken by companies in order to obtain their rights as employees in the company and nationally in Indonesia refers to the Job Creation Law and Government Regulation Number 35 of 2021. Referring to the point of view of human rights, obtaining information and education, including the rights of the community, one of them fulfills it through the fulfillment of employee rights in the work agreement with the company.